Frequencies of Helicobactor Pylori infection among Adult patients with Chronic Immune Thrombocytopenia: A comparative cross sectional study - sadia sultan (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Abstract Background: Many studies have reported an association between Chronic Immune Thrombocytopenia and Helicobactor Pylori infection. Significant improvement in platelet count is seen after eradication of Helicobactor Pylori infection. Objective: We looked for the frequencies of Helicobactor Pylori infection in patients with Chronic Immune Thrombocytopenia and clinico-hematological differences in two groups. Methods: A cross sectional descriptive study was conducted from January 2009 to December 2011. 110 chronic Immune thrombocytopenic patients and 40 control subjects were enrolled. Helicobactor Pylori infection was documented by Helicobactor pylori stool antigen (HpSA) enzyme immunoassay method (EIA). Frequencies were calculated. Chi-square test was used for comparison. P-value of less than 0.05 was considered significant. Results: Helicobactor Pylori infection in Chronic Immune Thrombocytopenic patients was seen in 45 cases (40.9%) and in 24 (60%) control subjects; the difference is not significant statistically. No significant differences were seen in H-Pylori positive and negative patients with respect to maternal characteristics and clinical features except for mean platelet count which was lower in Helicobactor Pylori negative group (P=0.035). Conclusion: Unlike many related studies, we found no significant difference between the frequencies of the cases versus controls. Low mean platelet count is seen in Helicobactor Pylori negative patients.